Development of bracelet type for vessel navigator using near-infrared ray - Seok Kim, Bong (International Journal of Engineering and Technology, 2018)
Background/Objectives: Bruises on skin or bent in blood vessel and needle stick might occur when a newly graduated nursewho is a poorly trained stuck the needle into wrong spot instead of blood vessel due to poor visibility of fat patients as well as young childrenMethods/Statistical analysisDevelopment of product design for vein finder with a bracelet form using near-infrared ray and securement of not only certificate authority for the device through the possible application of test progress in actual environment but product test specification.Findings: This study is a vessel finding device through near-infrared ray technology. Technology development for various kind of applied products which is able to give first aid to a first-aid patient will be able to be expected. Having technology in convergence field of industry in case of upgrade development of beam projection method which is directly project the back of the hand will be considered to occupy an advantageous position.Improvements/Applications: It is expected the device to be a good opportunityÂ to invigorate related research and development for optimizing performance in medical device industry even though poor R&D domestic environmentÂ